Membangun Moralitas Bangsa melalui Pendidikan Islam (Kontekstualisasi terhadap Pemikiran Pendidikan Islam al-Ghazali) - Irawan, Vaesol Wahyu Eka (MUNAQASYAH : Jurnal Ilmu Pendidikan dan Pembelajaran, 2020)
Moral education is very necessary to be applied in life to face the challenges of an increasingly advanced era like now. Moral education can be obtained by applying Islamic education whose orientation is not only for the needs of the world but also for the afterlife. Islamic education as an effort to shape people must be based on where all activities and all formulations of Islamic education goals are linked, namely the Koran and the Sunnah of the Prophet Muhammad SAW which can be developed with ijtihad. The basic concept of Islamic education in general is education in the context of shaping Muslim personality. The purpose of Islamic education is to form humans worshiping God based on the conditions of the place by considering geography, economics, and others in that place.